2015
DOI: 10.1093/europace/euv109
|View full text |Cite
|
Sign up to set email alerts
|

Longevity of implantable cardioverter-defibrillators for cardiac resynchronization therapy in current clinical practice: an analysis according to influencing factors, device generation, and manufacturer

Abstract: AimsDevice replacement at the time of battery depletion of implantable cardioverter-defibrillators (ICDs) may carry a considerable risk of complications and engenders costs for healthcare systems. Therefore, ICD device longevity is extremely important both from a clinical and economic standpoint. Cardiac resynchronization therapy defibrillators (CRT-D) battery longevity is shorter than ICDs. We determined the rate of replacements for battery depletion and we identified possible determinants of early depletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 18 publications
7
53
0
Order By: Relevance
“…Assuming a median CRT-D battery life of 5 years 6 and an incidence rate of 5 SCD per 1,000 patient-years in CRT-D and 20 in CRT-P, after computing the cumulative incidence of the event we calculated a patient-based NNT of 13.5 per battery life, or an annual NNT of 67.5. These represent the number of CRT patients who would need an ICD for one SCD to be prevented during the battery-life or a 12-month period, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming a median CRT-D battery life of 5 years 6 and an incidence rate of 5 SCD per 1,000 patient-years in CRT-D and 20 in CRT-P, after computing the cumulative incidence of the event we calculated a patient-based NNT of 13.5 per battery life, or an annual NNT of 67.5. These represent the number of CRT patients who would need an ICD for one SCD to be prevented during the battery-life or a 12-month period, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that ICD and CRT-D longevity may vary significantly between manufacturers, 35 thus impacting on healthcare costs. 6 However, currently available data refer to heterogeneous populations, cardiac devices, and time periods.…”
Section: Introductionmentioning
confidence: 99%
“…Data on CRT-D battery survival were obtained from a previously published report by Landolina et al22 Data on all patients who had received a CRT-D system between 2008 and 2010 according to international recommendations were prospectively collected in the hospital databases of nine Italian implanting centers. The comparison of longevity among recent-generation CRT-Ds from different manufacturers (e.g., Boston Scientific Corporation [BSC], St. Jude Medical [SJM] and Medtronic [MDT]) was performed only for subgroups with at least 100 devices in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The comparison of longevity among recent-generation CRT-Ds from different manufacturers (e.g., Boston Scientific Corporation [BSC], St. Jude Medical [SJM] and Medtronic [MDT]) was performed only for subgroups with at least 100 devices in the analysis. Recent-generation devices were identified as the most recent device families released onto the market, for the most part after 2007 22. The results from the study by Landolina et al22 showed that recent-generation BSC CRT-D devices have substantially longer battery life than CRT-D devices from the other two manufacturers, SJM and MDT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation